Use of biodegradable driftnets to prevent ghost fishing: physical properties and fishing performance for yellow croaker. (1st February 2016) - Kim, S.; Kim, P.; Lim, J.; An, H.; Suuronen, P.
Abstract: When synthetic non‐biodegradable fishing nets are lost, abandoned or discarded at sea, they may continue to catch fish and other animals for a long period of time. This phenomenon is known as 'ghost fishing'. Biodegradable fishing nets, on the other hand, are intended to degrade or decompose after a certain period of time under water and thereby lose their ghost fishing capacity more quickly than conventional gear. A biodegradable net material, a blend of 82% polybutylene succinate (PBS) and 18% polybutylene adipate‐co‐terephthalate (PBAT), was developed. We examined the physical properties and degradability of the biodegradable monofilament, and compared the fishing performance of driftnets made of conventional nylon and of the biodegradable material. When dry, conventional nylon monofilament exhibited a greater breaking strength and elongation than biodegradable monofilament of the same diameter. When wet, the biodegradable monofilament exhibited a stiffness of c . 1.5‐fold than nylon monofilament. This suggests that a net made of the less flexible biodegradable monofilament would have lower fishing efficiency than conventional nets. The fishing performance comparisons between the biodegradable and conventional nylon nets, however, revealed similar catch rates for yellow croaker Larimichthys polyactis . Biodegradable monofilament started to degrade after 24 months in seawater by marine organisms. We conclude that biodegradable netting may become a feasible alternative to conventional nylon netting and can contribute to reducing the duration of ghost fishing. Nonetheless, there remain many uncertainties, challenges and knowledge gaps that have to be solved before we are able to draw firm conclusions about the overall benefits of these materials in driftnet fisheries. Abstract : When synthetic non‐biodegradable fishing nets are lost, abandoned or discarded at sea, they may continue to catch fish and other animals for a long period of time. This phenomenon is known as 'ghost fishing'. Biodegradable fishing nets, on the other hand, are intended to degrade or decompose after a certain period of time under water and thereby lose their ghost fishing capacity more quickly than conventional gear. A biodegradable net material, a blend of 82% polybutylene succinate (PBS) and 18% polybutylene adipate‐co‐terephthalate (PBAT), was developed. We examined the physical properties and degradability of the biodegradable monofilament, and compared the fishing performance of driftnets made of conventional nylon and of the biodegradable material. The fishing performance showed that similar catches of yellow croaker were caught with both types of fishing net. We conclude that biodegradable netting may become a feasible alternative to conventional nylon netting and can contribute to reducing ghost fishing.